2021
DOI: 10.3390/agronomy11030602
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement to Salt Stress Tolerance in Strawberry Plants by Iodine Products Application

Abstract: Iodine is a non-essential element for land plants, but is considered as a beneficial element, related to antioxidant capacity, environmental adaptations and improvement of plant growth. Salinity is one of the more recurrent abiotic stresses worldwide, seriously affecting vegetal production. The aim of this work was to evaluate iodine application (Q products® and KIO3, Quimcasa de México, Naucalpan, Mexico) in strawberry plants under normal and salt stress conditions. Growth, antioxidant content, essential mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…2 , 3 ). These results were consistent with a series of previous studies carried out, for example, in lettuce 3 or strawberry 25 . In a recent study on tomato, three foliar applications of 100 μM KIO 3 caused a 23% improvement in fruit yield in plants subjected to salinity stress (100 mM NaCl) during most of the growing cycle, without preventing the loss of plant biomass triggered by NaCl 47 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…2 , 3 ). These results were consistent with a series of previous studies carried out, for example, in lettuce 3 or strawberry 25 . In a recent study on tomato, three foliar applications of 100 μM KIO 3 caused a 23% improvement in fruit yield in plants subjected to salinity stress (100 mM NaCl) during most of the growing cycle, without preventing the loss of plant biomass triggered by NaCl 47 .…”
Section: Discussionsupporting
confidence: 93%
“…Also, there was a need to confirm that the low micromolar doses that were effectively used in Arabidopsis would still be effective in tomato in a commercial production setting. Furthermore, the potential role of iodine in resilience to abiotic stresses as found in Arabidopsis 15 and supported by a series of scattered but consistent bibliographic indications 3 , 18 , 25 had to be confirmed.…”
Section: Discussionmentioning
confidence: 96%
“…Previous investigations of I biofortification peculiarities revealed that potassium iodide application reduced Na accumulation in lettuce seedlings [44]; the latter outcome is consistent with the Na content decrease by almost twice recorded in chervil treated with I, in the present research. Literature reports indicate that both Se and I can alleviate salt stress in plants [45,46].…”
Section: Macro-elementsmentioning
confidence: 99%
“…Crops that grow in high concentrations of salts tend to reduce their development and growth; therefore, production is reduced [7,26,27]. Salt stress in plants causes osmotic stress, which triggers plants to consume extra energy to absorb water and nutrients [28,29].…”
Section: Seedling Biomass and Growth Parametersmentioning
confidence: 99%